Evaluation of the Policy of Granting State Land Tenure Rights in Sambaliung District, Berau Regency - Hermansyah, Hermansyah; Darmawan, Arif; Handoko, V. Rudy (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to find out and analyze the evaluation of the policy of granting state land tenure rights in Sambaliung District, Berau Regency and identify the factors inhibiting the implementation of Berau Regency Regional Regulation Number 5 of 2019 concerning the Implementation of State Land Tenure Administration. This research is a descriptive qualitative research and the results of the study show that the evaluation of Berau Regency Regional Regulation Number 5 of 2019 shows that although this policy has provided several positive achievements, there are still challenges that need to be overcome to improve its effectiveness and responsiveness.